The Mediation Role of Perceived Benefits and Barriers in the Relationship Between Support Provided by Significant Others and Physical Activity of Adolescents - Rodrigues, F. (2023)
We investigated whether the relationship between significant others’ social support and adolescents’ physical activity (PA) is mediated by perceived barriers and benefits of PA. In this cross-sectional study, we analyzed data from 497 adolescents (girls = 272, boys = 225) aged between 12-18 years (M = 15.87, SD = 1.43) from six different middle and secondary schools. We collected data regarding social cognitive variables and PA with self-report measures and calculated the metabolic equivalent of total amount PA. We performed structural equation modeling and mediation analyses and found our proposed models fit the data. In girls, perceived PA benefits mediated the association between support provided by friends (β = .13; IC 95% = .02 .29), a best friend (β = .14; IC 95% = .03, .33), and parents (β = .07; IC 95% = .01, .18), and PA. Similarly in boys, perceived PA benefits partially mediated the association between support provided by parents (β = .09; IC 95% = .04, .37), friends (β = .11; IC 95% = .05, .40), and a best friend (β = .10; IC 95% = .05, .40) and PA. Perceived barriers to PA did not display any significant mediation role for either sex. Interventions to foster others’ support for PA, especially from a best friend, are important for promoting PA among adolescents.